Pesquisa de genomas virais em primatas não humanos do novo mundo por metagenômica - Ullmann, Leila Sabrina [UNESP] (2014)
Wild animals-borne emerging zoonoses represent the most significant and growing threat to global health. Non-human primates contribute with 20% of major human diseases, as they are considered the main experimental model and also can be considered sentinels for different diseases that affect humans. The aims of the present thesis were to develop a viral metagenomics protocol to detect sequences from viruses in plasma from captive New World non-human primate species (Saimiri sciuratus, Aotus ainfulatus, Alouatta guariba e Sapajus apella) from National Primate Center (Belém, PA), Bela Vista Biological Sanctuary (BVBS, Foz do Iguaçu, PR), and Tietê Ecological Park (São Paulo, SP). The Illumina technology (MiSeq) was used for deep sequencing, and a bioinformatics pipeline was developed in order to analyze the sequences obtained. Overall, genomes corresponding to different viral families were identified from plasma, and emphasis was given to torque tenus virus, hepatitis G virus types A and B, parvovirus, and pappilomavirus. A new whole-genome sequence from Hepacivirus genus, Flaviviridae family, was identified in monkeys from Southern Brazil. The results demonstrate the wide variety of viral genomes present on clinically healthy New World monkeys and highlight the importance of studies that aim to identify possible emerging viruses